Formal representation of knowledge using Z in fast breeder test reactors. (14th July 2009) - Sankar, Bindu; Seetha, H.; Kuriakose, K.K.; Satyamurty, S.A.V.; , P. Swaminathan
In this paper, knowledge representation using Z, a formal notation, is adapted in mapping Fast Breeder Test Reactor (FBTR) requirements. The most frequent cause of faults in safety-critical real-time computer systems is traced to fuzziness in representing requirements knowledge. Pitfalls using a natural language as a medium for representing the system requirements knowledge were analysed and explored. To ensure the specified safety, it is necessary to represent the system requirements of safety-critical real-time computer systems using formal mathematical methods. This removes the fuzziness in communicating knowledge on reactor system requirements. This paper contains the formal mathematical model for requirement specifications of FBTR systems using Z notation. Finally, the advantages of using formal representation for representing system requirements knowledge of FBTR using Z notations to minimise the ambiguity in knowledge communication and thus improve the safety are summarised.